Non-Taylor Series Based Positioning Method for Hybrid GPS/Cellphone System - Liew, S. C.; Tan, K. G.; Tan, C. P. (2006)
This paper has discussed in detailed the conventional Taylor series based and the proposed non-Taylor series based positioning methods for hybrid GPS/Cellphone. The proposed positioning method is a simpler positioning method which involves less complicated mathematical computation, and it is able to provide more accurate positioning results. Furthermore, no initial estimation of A-GPS receiver's position is required in non-Taylor series based positioning. Positioning computation is done for the cases with and without round trip delay (RTD), and also for cases with and without the presence of noises and delays.